2005
DOI: 10.1007/bf03015781
|View full text |Cite
|
Sign up to set email alerts
|

Another method to assist nasogastric tube insertion

Abstract: In light of the results of most recent studies showing better survival of surgical patients with tight glycemic control the preservation of intraoperative normoglycemia gains clinical relevance.1 Epidural anesthesia in the absence of general anesthesia has long been recognized to suppress the hyperglycemic and endocrine responses to pelvic surgery. 2 The failure of epidural anesthesia combined with inhalation anesthesia to maintain glucose homeostasis during major abdominal surgery was traditionally ascribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 4 publications
1
39
0
Order By: Relevance
“…org/nasogastric-tube-insertion-the-simple-yet-impossible/ accessed 11 Nov 2016). Table 2 shows different RCTs concering NGT insertion methods [62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: By Equipment Minor Majormentioning
confidence: 99%
See 1 more Smart Citation
“…org/nasogastric-tube-insertion-the-simple-yet-impossible/ accessed 11 Nov 2016). Table 2 shows different RCTs concering NGT insertion methods [62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: By Equipment Minor Majormentioning
confidence: 99%
“…Mahajan et al [70] 2005 After introduction into the oropharynx, the orogastric tube or Murphy's eye of tube is directed into the esophagus along the lateral pharyngeal wall using a gloved left index finger Cohen et al [75] 1963 NGT is inserted through the nose and mouth where its tip is grasped with a Magill forceps under laryngoscopic visualization. The NGT is retracted from the mouth until approximately 3 inches remain from the nares.…”
Section: %mentioning
confidence: 99%
“…Insertion of a gastric tube can be a difficult and frustrating experience, especially in patients who are anesthetised, paralysed and sedated [1][2][3][4][5][6][7]. Ozer and Benumof [8] have found that the most common sites of impaction of orogastric and nasogastric tubes are the pyriform sinuses and arytenoids cartilages, leading to coiling in the oropharynx.…”
Section: Trachlight Assisted Insertion Of Nasogastric Tubementioning
confidence: 99%
“…In our experience, in addition to the impaction of the tube against these structures, the basic design of the tube contributes to tube coiling in the oropharynx. The distal 6 cm of the gastric tube has multiple holes that are weak points [2]. Once the tube is impacted against the pyriform sinuses or arytenoids cartilage, bending of the tube occurs at these points, thereby promoting coiling and retarding its entry into the oesophagus [2,8].…”
Section: Trachlight Assisted Insertion Of Nasogastric Tubementioning
confidence: 99%
See 1 more Smart Citation